Some numerical methods for temperature and mass transfer simulation on the dehydration of herbs - Islam, Md. Rajibul; Alias, Norma (International Association of Computer Science and Information Technology Press (IACSIT), 2010)
Advances in herbs based products preservation and technologies are very significant in order to reduce post-harvest losses. The dynamic mathematical model of concurrent heat and moisture transfer are being established for the simulation of temperature and moisture distributions inside the herbs material during dehydration potential of herbs in a slab-shaped solid. Mathematical modeling presents the exchange of heat and mass transfer between material and drying air. Finite-difference method (FDM) based on Crank-Nicolson was used to discretise a parabolic type partial differential equations (PDE). The key purpose of this study is to illustrate the simulation of tropical herbs’ dehydration through some numerical methods such as Jacobi, Gauss-Seidel and Red-Black Gauss-Seidel. This study focuses on the implementation of sequential algorithms on the simulation. 3D geometric visualization by COMSOL Multiphysics and graphical numerical results of FDM approximation in mass and heat transfer demonstrate the results of this study. The contribution of this study is a flourishing and modified mathematical simulation in representing the concrete process of dehydration in herbs product based industry. Most thermal and moisture models are empirical rather than theoretical. Therefore, the novelty of this paper is the best sources of thermal and moisture data for the commercial tropical herbs dehydration derived from the mathematical model in order to avoid high prototype costs and to improve inaccurate conditions and process parameters with the advancement of dryer technologies. The computational platform is based on Intel®Core™2Quad processors with MATLAB software. The performance analyses of Numerical methods are presented in terms of execution time, computational complexity, number of iterations, errors, accuracy and convergence rate.